2018
DOI: 10.1007/s12144-018-9861-3
|View full text |Cite
|
Sign up to set email alerts
|

You make all things special: Developing a scale to measure sympathetic magic in romantic relationships

Abstract: This paper describes the development and construct validation of the Romantic Sympathetic Magic Scale (RSMS). The scale measures individual differences in directing attachment behavior toward inanimate objects associated with one's partner. We offer a theoretical basis for such behavior in the concept of sympathetic magic and test the motivational and cognitive factors involved in this tendency. Finally, we differentiate romantic sympathetic magic from similar concepts. Three studies (N = 851) showed that RSMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…On the other hand, chronic attempts to distance oneself in distressing situations of intimacy observed in avoidant attachment orientation (Mikulincer et al, ) were negatively related to attachment to inanimate objects associated with one's partner. These correlations have been replicated in several studies (Niemyjska, Gieszczyk, Markowska, & Pajączkowska, , Study 1–3; Niemyjska & Parzuchowski, , Study 1–3).…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…On the other hand, chronic attempts to distance oneself in distressing situations of intimacy observed in avoidant attachment orientation (Mikulincer et al, ) were negatively related to attachment to inanimate objects associated with one's partner. These correlations have been replicated in several studies (Niemyjska, Gieszczyk, Markowska, & Pajączkowska, , Study 1–3; Niemyjska & Parzuchowski, , Study 1–3).…”
Section: Introductionmentioning
confidence: 63%
“…Indeed, Wildschut et al (, Study 7) showed that nostalgia increases a general sense of one's social competence (i.e., initiation of social relationships, self‐disclosure, and providing emotional support to others). I would not expect that attachment to inanimate objects affects the evaluation of one's social competence in general, but it might increase the perceived quality of a specific relationship (e.g., with one's romantic partner; Niemyjska & Parzuchowski, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations